2015
DOI: 10.1093/hmg/ddv493
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study identifiesTXNIPgene associated with type 2 diabetes mellitus and sustained hyperglycemia

Abstract: Type 2 diabetes mellitus (DM) is an established risk factor for a wide range of vascular diseases, including ischemic stroke (IS). Glycated hemoglobin A1c (HbA1c), a marker for average blood glucose levels over the previous 12 weeks, is used as a measure of glycemic control and also as a diagnostic criterion for diabetes (HbA1c levels ≥ 6.5%). Epigenetic mechanisms, such as DNA methylation, may be associated with aging processes and with modulation of the risk of various pathologies, such as DM. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
106
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 63 publications
14
106
1
Order By: Relevance
“…Previous studies reported DMPs (including cg19693031) at the TXNIP gene to be inversely correlated with both type 2 diabetes and sustained hyperglycaemia (for example, haemoglobin A1c levels)5455. In our data set of T1D patients, we also found cg19693031 to be a DVP in monocytes ( P =9.1 × 10 −4 ); this observation suggests that a proportion of DVPs result from the diabetes-associated metabolic effect.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies reported DMPs (including cg19693031) at the TXNIP gene to be inversely correlated with both type 2 diabetes and sustained hyperglycaemia (for example, haemoglobin A1c levels)5455. In our data set of T1D patients, we also found cg19693031 to be a DVP in monocytes ( P =9.1 × 10 −4 ); this observation suggests that a proportion of DVPs result from the diabetes-associated metabolic effect.…”
Section: Discussionsupporting
confidence: 70%
“…Similar studies with remarkable findings in the investigation of a variety of diseases as type 2 diabetes mellitus (Soriano-Tarraga et al 2016), psoriasis (Zhou et al 2016), schizophrenia (Montano et al 2016), metabolic syndrome/obesity (Ali et al 2016) and many others have been recently published. It is expected that the new technologies that make possible this type of works and the technologies that will come allow epigenetic epidemiology to reach major objectives as the complete description of the epigenetic processes shaping the development of organisms, the interactions gene-epigene and epigene-environment, the establishment of the role of epigenetics in risk and emergence of diseases, as marker of disease or exposure, and the mechanisms of the inheritance of epigenetic changes over generations in humans (Bollati & Baccarelli 2010;Bakulski & Fallin 2014).…”
Section: Environmental Epigeneticssupporting
confidence: 67%
“…PI051737) [43,44]. Inclusion criteria in BASICMAR cohorts were as follows: (1) first-ever IS, (2) brain imaging with CT or MRI, (3) availability of clinical data supporting the assigned stroke subtype according to TOAST classification [45], (4) absence of intracranial hemorrhage, neoplasms, demyelinating and autoimmune diseases, and vasculitides.…”
Section: Methodsmentioning
confidence: 99%
“…Sample and CpG quality controls and the statistical analysis were performed as described in Soriano-Tarraga et al [44]. Initial quality control of sample data was conducted using GenomeStudio version 2011.1 (Illumina, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%